Examination of the Role of Family Socioeconomic Status and Parental Education in Predicting English as a Foreign Language Learners' Receptive Skills Performance - Nining Suningsih (Journal of English as A Foreign Language Teaching and Research, 2022)
There is a stereotype of a correlation between family socioeconomic status and parental educational background with the student's achievement. Therefore, this study aims to know in-depth roles. Examine 60 students of Melati Junior High School Samarinda in their performance on reading and listening comprehension tasks. There is a significant relationship between SES and parents' educational background using the correlational method, non-experimental. Nevertheless, it s not always that students with low socioeconomic and parents' educational backgrounds get low scores and vice versa. Likewise, students with high educational backgrounds of their parents do not necessarily get high grades in school. Several factors revealed that SES and Educational background is the main predictor of academic achievement.